RETRACTED: G-20 economies and their environmental commitments: Fresh analysis based on energy consumption and economic growth - Li, Puying; Akhter, Mohammad Javeed; Aljarba, Ahmed; Akeel, Hatem; Khoj, Haitham (Frontiers in Environmental Science, 2022)
The impact of economic growth and energy use is still controversial regarding sustainability, and researchers have limited consensus in this regard. Electricity is considered more friendly regarding the environmental issues against direct fossil fuel consumption. However, many developed economies still depend on fossil fuel sources for electricity generation. Therefore, this study attempted to verify the relationship between electricity consumption with carbon emission in developed economies like Group twenty (G-20). Economic growth and foreign direct investment are the other important variable for analyzing this relation. For this purpose, a dataset was generated between 1995-2018. The study used econometric methods such as cross-sectional dependence, cointegration, Fully Modified Ordinary Least Square (FMOLS), Dynamic Ordinary Least Square (DOLS) estimators, and the Pair-wise panel Granger causality test to view the latest picture of the relationship between the dependent and independent factors. Surprisingly, the outcome of electricity consumption shows a positive relationship with the growth of CO2. It indicates that electricity production is still dependent on the sources that help increase the CO2 emission in G-20. Furthermore, the outcomes of GDP and its square term confirm the notion of the Environmental Kuznets Curve (EKC) for these economies. These results suggest that policymakers promote green and clean electricity sources for sustainable economic growth.